PENDEKATAN INKUIRI-KONTEKSTUAL BERBASIS TEKNOLOGI INFORMASI UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS MAHASISWA - Mahmudatusaadah, Ai (INVOTEC, 2011)
Food additive is one of the topics included in the food chemistry course. Despite its benefits which are directly related to everyday life applications, it is common knowledge that the chemistry is one of the subjects that are difficult to understand for its abstraction. Students’ average mastery of food chemistry is below 60%. The study found that information technology-based contextual inquiry approach to topic of food additives can improve students’ critical thinking skills. Increase in scores from pretest to posttest is experienced by all samples with different N-Gain values. The majority (59%) is in medium category, 20% in high category and a fraction (11%) is in low category. Information technology-based contextual inquiry approach to the topic of food additives makes students more active and increases learning enthusiasm